miRNA expression haplotype in Hispanics with endometriosis - Alday-Montañez, Flor Daniela; Lariz-Nevárez, Brandon Daniel; Carrasco-Urrutia, Víctor Josué; Dickens-Terrazas, Daniel; Barragán-Farías, Adali; Mejía-Carmona, Gloria Erika; Kirken, Robert Arthur; Bencomo-Alvarez, Alfonso Enrique; Lobo-Galo, Naún; Vargas-Caraveo, Alejandra; Díaz-Sánchez, Ángel Gabriel; Robles-Escajeda, Elisa; et al. (Frontiers in Reproductive Health, 2025)
BackgroundEndometriosis affects approximately 10% of women of reproductive age; this prevalence may be underestimated, mostly in developing countries, including Mexican and Hispanic populations, due to socioeconomic barriers and limited access to specialized diagnosis. Although laparoscopy remains the gold standard for diagnosis, highlighting the need for non-invasive biomarkers. Haplotype expression of specific miRNAs acts as a circulating signature in both healthy and disease states, including endometriosis. However, their applicability in Hispanic populations has been unexplored.MethodThis study evaluated the discriminatory capacity of a miRNA expression haplotype in the blood plasma of a Hispanic cohort with laparoscopic confirmed diagnosis (15 patients with endometriosis and 7 from a reference group). The expression levels of miR-451a, miR-3613, miR-125b, let-7b, miR-150, and miR-342 were quantified using qRT-PCR, and their diagnostic performance was assessed through individual ROC curves and multivariate classification models: Logistic regression, CRT, and stacking-based ensemble model.ResultsThe miRNA expression haplotype demonstrated high diagnostic accuracy with logistic regression (AUC = 0.914), CRT (AUC = 0.990), and an ensemble model using stacking (AUC = 0.990). Individually, miR-451a (AUC = 0.79), miR-3613 (AUC = 0.714), and let-7b (AUC = 0.667) were the most relevant markers and demonstrated more relevance in the expression haplotype.ConclusionThese findings suggest that a miRNA-based diagnostic panel could provide a highly sensitive and specific alternative for diagnosing endometriosis in Hispanic populations. However, validation in larger cohorts is essential to confirm reproducibility and assess its clinical utility in different healthcare settings.